Belanja Online di Masa Pandemi Covid-19: Studi Kasus Ibu-ibu Rumah Tangga di Kota Makassar - Andi Maghfirah Juniar; Jusrianti Jusrianti (Universitas Muslim Maros, 2021)
In early 2020 the world was shocked by the outbreak of a new type of virus (SARS-CoV-2) known as Corona virus disease 2019 (abbreviated as Covid-19), whose first case was discovered at the end of December 2019 in Wuhan, China. The outbreak of the Covid-19 was known to have entered Indonesia in mid-March 2020, resulting in Indonesia entering the Disaster Emergency Period. The entry of Covid-19 in Indonesia prompted the government to adopt a Large-Scale Social Restriction (PSBB) policy to stop the wider spread of Covid-19. With this policy, people's activities outside the home are limited, and more people's activities are diverted at home, including shopping online through applications. In this context, the ease of shopping online may resulted in consumptive behavior when one can't control him/herself. This research was conducted between September and November 2020 in the city of Makassar City. Makassar was chosen because based on online observations, many housewives in the Makassar area tend to behave consumptively during the outbreak Covid-19. This can be seen from the habit of shopping online which is supported by technology and the ease of accessing online applications. Data was collected through in-depth interviews and observation. Those who participated in this study were ten housewives who had a history of routine shopping online using a shopping application. The study indicates that the Covid-19 pandemi has limited people's mobility, one of which is social restriction policies issued by the government which has changed many aspect of human life, including their shopping method. This shopping method has changed from direct shopping through which human interaction occurs to more often online shopping, using online shopping applications. Housewives perceive online shopping in various ways, from relating it to the simplicity of shopping; transaction process using advanced technology; to shopping by using online shopping applications. The reasons why online shopping is in favour among housewives during the Covid-19 pandemi are the availability of a variety of offered goods, its convenience and practicality, its safety and comfort, and its discount offers. During the Covid-19 pandemi, this way of shopping intensifies. In addition to its advantages, online shopping also has weaknesses, namely the discrepancy between the appearance of the goods ordered and the reality of the goods received; the purchased goods cannot be received directly because it requires delivery time; vulnerability to damage to goods in the shipping process, and vulnerability to fraud. Therefore, consumers must consider the needs and desires in order to be able to control themselves in shopping because not all the desired items are needed items. In addition, fraud is vulnerable in online shopping. Thus consumers not only have to question the goods to be purchased in as much detail as possible; selective in choosing online stores; but also one must identify the track record of intended online store.